Towards digital transformation: Lessons learned from traditional organizations1. (26th March 2018) - Loonam, John; Eaves, Sally; Kumar, Vikas; Parry, Glenn
Abstract : Digitally enabled organizations are supported by new information and communication technologies, referred to as digital technologies, which increasingly promise enormous opportunities for growth. The study reviews 10 case studies from the literature and analysis the approaches these organizations have taken to successfully implement digital technologies. The findings reveal a conceptual framework that seeks to support management in understanding the actions required to implement digital transformation.